Late Peaks of HMGB1 and Sepsis Outcome: Evidence For Synergy With Chronic Inflammatory Disorders. Issue 3 (September 2019) - Karakike, Eleni; Adami, Maria-Evangelia; Lada, Malvina; Gkavogianni, Theologia; Koutelidakis, Ioannis M.; Bauer, Michael; Giamarellos-Bourboulis, Evangelos J.; Tsangaris, Iraklis
Abstract : ABSTRACT: High mobility group box 1 (HMGB1) is released from macrophages as a late biomarker of sepsis. Conditions associated with pre-existing macrophage activation may modify HMGB1 expression. This study aimed to assess the impact of HMGB1 kinetics on 28-day mortality. In a sub-study of a previous randomized clinical trial among patients with systemic inflammatory response syndrome and gram-negative infections, patients were classified in early and late HMGB1 peak groups. Serial measurements of HMGB1, ferritin and interferon-gamma (IFNγ) were performed in all available sera. Two hundred ten patients were included; 118 (46.5%) had at least one inflammatory disease (diabetes, chronic obstructive pulmonary disease, chronic heart failure, or chronic renal disease). Mortality after 28 days was higher among patients with a late peak of HMGB1 (OR 2.640; P  = 0.026). Co-existence of late peak and inflammatory disease synergistically impacted mortality (odds ratio of logistic regression analysis 3.17; P : 0.027). Late peak was concomitantly associated with higher values of ferritin ( P  = 0.035), and IFNγ ( P  = 0.002) among patients with hyperferritinemia. It is concluded that late HMGB1 peak was associated with worse prognosis, especially in patients with underlying chronic inflammatory conditions.